Enhanced Photocatalytic Activity of W-Doped and W-La-Codoped TiO2 Nanomaterials under Simulated Sunlight. (21st October 2014) - Hua, Chenghe; Dong, Xiaoli; Wang, Xiuying; Xue, Mang; Zhang, Xiufang; Ma, Hongchao
Abstract : W-doped TiO2 and W-La-codoped TiO2 nanomaterials were successfully synthesized via the sol-gel method. The products were characterized by X-ray diffraction, UV-vis diffuse reflectance spectrophotometer, transmission electron microscopy, and X-ray photoelectron spectroscopy. The presence of W and La results in significant red shift of absorption edge for TiO2 -based nanomaterials. The weight ratios of La and W in the composites play important roles in the absorption edge for TiO2 -based nanomaterials. The photocatalytic activities of both W-doped TiO2 and W-La-codoped TiO2 photocatalysts for decolorization of methyl orange solution were evaluated under simulated sunlight irradiation. The results showed that both W-doped and W-La-codoped can effectively improve the photocatalytic behaviors of TiO2 nanomaterials ascribed to the improved photoinduced charge carriers separation, enhanced light absorption, and large surface area. Furthermore, W-La-codoped TiO2 exhibited higher photocatalytic activity than W-doped TiO2 . Considering their high photocatalytic activity, the doped TiO2 nanomaterials could be applied in wastewater treatment and environmental purification.